Klebsiella pneumoniae Complex Harboring mcr-1, mcr-7, and mcr-8 Isolates from Slaughtered Pigs in Thailand - Nattamol Phetburom; Parichart Boueroy; Peechanika Chopjitt; Rujirat Hatrongjit; Yukihiro Akeda; Shigeyuki Hamada; Suphachai Nuanualsuwan; Anusak Kerdsin (Microorganisms, 2021)
Dissemination of the mobile colistin resistance gene mcr in Enterobacterales among humans, animals, and the environment is a public health issue. We characterized mcr genes in the Klebsiella pneumoniae complex (KpnC) isolated from slaughtered pigs in Thailand. The 280 KpnCs consisted of K. pneumoniae (85%), Klebsiella quasipneumoniae (8.21%), and Klebsiella variicola (6.79%). mcr genes were detected in 6.79% (19/280) of KpnC isolates, consisting of mcr-8 (n = 9; 3.21%), mcr-7 (n = 7; 2.50%), mcr-7 + mcr-8 (n = 2; 0.71%), and mcr-1 + mcr-7 (n = 1; 0.36%). K. pneumoniae predominantly carried the mcr-7 and mcr-8 genes, while K. variicola and K. quasipneumoniae harbored mcr-7 and mcr-8, respectively. Six of the nineteen mcr-harboring KpnC isolates exhibited colistin resistance, and five had mcr-1 or mcr-8 transferable to an Escherichia coli recipient. Antimicrobial susceptibility analysis revealed that all mcr-carrying KpnC isolates were susceptible to carbapenems, cefotaxime, cefepime, amoxicillin/clavulanic acid, piperacillin/tazobactam, amikacin, and fosfomycin, and had high resistance to azithromycin. Multilocus sequence analysis demonstrated that the mcr-harboring KpnC isolates were genetically diverse. A ‘One-Health’ approach is useful to combat antimicrobial-resistant bacteria through coordinating the human, animal, and environmental sectors. Hence, continuous monitoring and surveillance of mcr-carrying KpnCs throughout the pork supply chain is crucial for ensuring public health.